Biological mechanism study of meditation and its application in mental disorders - Donghong Cui (General Psychiatry, 2020)
In recent years, research on meditation as an important alternative therapy has developed rapidly and been widely applied in clinical medicine. Mechanism studies of meditation have also developed progressively, showing that meditation has great impact on brain structure and function, and epigenetic and telomere regulation. In line with this, the application of meditation has gradually been expanded to mental illness, most often applied for major depressive disorders and substance-related and addictive disorders. The focus of this paper is to illustrate the biological mechanisms of meditation and its application in mental disorders.